Linguistic Intuitions and Cognitive Penetrability - Michael Devitt (Baltic International Yearbook of Cognition, Logic and Communication, 2014)
Metalinguistic intuitions play a very large evidential role in both linguistics and philosophy. Linguists think that these intuitions are products of underlying linguistic competence. I call this view “the voice of competence” (“VoC”). Although many philosophers seem to think that metalinguistic intuitions are a priori many may implicitly hold the more scientifically respectable VoC. According to VoC, I argue, these intuitions can be cognitively penetrated by the central processor. But, I have argued elsewhere, VoC is false. Instead, we should hold “the modest explanation” (“ME”) according to which these intuitions are fairly unreflective empirical theory-laden central-processor responses to phenomena. On ME, no question of cognitive penetration arises. ME has great methodological significance for the study of language. Insofar as we rely on intuitions as evidence we should prefer those of linguists and philosophers because they are more expert. But, more importantly, we should be seeking other evidence in linguistic usage.
Keywords: metalinguistic intuitions; cognitive penetration; linguistic usage; central processor